Primary leiomyosarcoma of cervical spine invading the vertebra without obvious osteoclasia: Case report and literature review. (4th July 2022) - Sun, Han; Zhuang, Min; Cheng, Dong; Zhu, Chenlei; Liu, Zhiwei; Qiu, Xubin
Abstract : Context: Primary leiomyosarcomas are malignant tumors of smooth muscles, with few reported cases occurring in the cervical spine. The authors report a case involving a 29-year-old man with primary leiomyosarcoma in the spinal canal posterior to the C3–C5 vertebrae. Findings: No obvious osteolytic lesions could be found in neither X-ray nor computed tomography scan. Because of the confusion of nontypical imaging findings, a decompressive surgery of anterior cervical corpectomy of C4 and reconstruction with a mesh cage filled with allogenic bone grafts were performed. The patient refused a second operation and then was advised to receive the radiotherapy. No recurrence of the symptoms was evident 6 months after surgery. Conclusion: When a patient suffers from upper cervical tumor, the leiomyosarcoma should be kept in mind as possible diagnoses despite its low occurring ratio. Early detection, early diagnosis, and early treatment must be the goal of the strategy.